Hubungan Kecerdasan Emosional Dengan Sikap Kepemimpinan Pengurus Organisasi Siswa Intra Sekolah - Tri Putri Handayani; Rini Hayati (Program Studi Bimbingan Penyuluhan Islam Fakultas Dakwah dan Komunikasi, 2020)
Abstract: This study aims to determine correlation emotional intelligence and student council leadership attitudes in SMA Negeri 6 Medan 2019-2020 academic year. This type of research is a quantitative study with a correlation approach. The data instrument used data scales emotional intelligence and leadership attitude student counsil, with a total sample of 44 students. The results of the research using the product moment correlation test, from the calculation results obtained that the correlation coefficient between emotional intelligence and the leadership attitude of the Student Council of Student Council (OSIS) is rcount = 0.668> rtable = 0.297, thus it can be concluded that there is a corelation emotional intelligence and the leadership attitude of OSIS administrators in SMA Negeri 6 Medan.